Effect of Probiotic Supplementation on Sprague Dawley Rat Liver Histopathology Fed by High Fat High Fructose Diet - Ninung Rose Diana Kusumawati (Diponegoro University, 2021)
Background: Non-alcoholic fatty liver disease (NAFLD) is an important cause of liver disease burden worldwide. The gastrointestinal microbiota has a close relationship with the liver as the liver is most exposed to intestinal bacteria. Microbial manipulation is a potential and effective therapy as an alternative in the management of NAFLD/NASH. It has been found that probiotics prevent NAFLD/NASH. However, the study about the protective effect of probiotics on NAFLD/NASH is still limited.